Indonesia - angelica kinanti oktavia simatupang (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2020)
This study aims to see how much influence the Locally Generated Revenue, General Allocation Fund, and Special Allocation Fund on Capital Expenditures in the districts/cities of North Sumatra province. The study involved 33 districts/cities in North Sumatra for the period 2016-2018. Data was taken from BPS North Sumatra. The sample criteria method used in this study is saturated samples, which means that all populations are sampled. The method used to analyze the data of this study is the multiple linear regression analysis method. From this research, it is found that PAD has no effect on capital expenditure, DAU has a positive and insignificant effect on capital expenditure, DAK has no effect on capital expenditure.